Antibiotic susceptibility and prevalence of Methicillin-resistant Staphylococcus aureus in different clinical isolates in a tertiary care hospital - Chaudhury, Nabamita; Biswas, Tanusri; Mondal, Raston; Aroni Chatterjee,; Saswati Chattopadhyay,; Nag, Soumi (Asian Journal of Medical Sciences, 2022)
Background: Staphylococcus aureus is a Gram-positive cocci bacterium responsible for variety of infections. Emergence of Methicillin-resistant S. aureus (MRSA) strains has led to a greater threat in different clinical settings. Early identification of MRSA in different infections is an effective measure to prevent and treat such systemic infections. Aims and Objectives: This study aims to isolate and identify MRSA with their antibiotic sensitivity in different clinical samples. Materials and Methods: A total of 2041 clinical samples from January to June 2021were collected and processed at the Microbiology Department of Burdwan Medical College and Hospital. S. aureus was identified and their antibiotic susceptibility testing was determined. MRSA/methicillin-sensitive S. aureus (MSSA) were identified by cefoxitin disc (30 mcg/disc) and their susceptibility to vancomycin and MIC determined by Etest following British Society for Antimicrobial Chemotherapy (BSAC) guidelines. Results: Of 2041 samples, 358 (13.36%) isolates were S. aureus, of which 207 (57.82 %) MRSA and 151 (42.18%) MSSA. Among the 207 MRSA isolates, 40% were from patients with sepsis, 18.36% from pyrexia of unknown origin, 12.56% from surgical site infection, and 10.62% from ventilator-associated events. The highest number (55.55%) of MRSA was isolated from blood followed by 27.05% of isolates were from pus. All the isolates were sensitive to vancomycin with MICs of 0.5 μg, 0.75 μg, 1.0 μg, and 1.5 μg according BSAC and also very good sensitivity to levofloxacin and piperacillin/tazobactam. Conclusion: The increasing prevalence of MRSA is posing a real threat to the health-care system. Careful detection and judicious use of antibiotics are the only answer.